Management of Chronic Urticaria : A Systematic Review of Allergic and Immunology - Ade Rahmanda Kamil; Robby Alfadli (International Medical Journal Corp. Ltd, 2025)
Introduction: Chronic urticaria (CU), characterized by recurrent wheals and/or angioedema lasting over six weeks, presents a significant therapeutic challenge due to its heterogeneous pathophysiology and frequent inadequate response to first-line H1-antihistamines. The expanding arsenal of biologics and immunomodulators necessitates a comprehensive synthesis of their comparative efficacy and safety. Methods: A systematic review was conducted following a predefined protocol to identify and synthesize evidence from randomized controlled trials, systematic reviews, and meta-analyses focusing on allergic and immunological treatments for chronic spontaneous urticaria (CSU). Studies were screened based on population, treatment focus, design, and outcome criteria. Data extraction encompassed treatment details, patient characteristics, effectiveness outcomes, safety profiles, and study quality. Evidence was synthesized narratively and quantitatively where possible. Results: The review included 66 studies. Second-generation H1-antihistamines are effective first-line therapy, with up-dosing providing modest additional benefit at the cost of increased somnolence (Phinyo et al., 2020; Xiao et al., 2022, 2023). For antihistamine-refractory CSU, omalizumab 300 mg every 4 weeks is highly effective and safe, with rapid and sustained improvements in urticaria activity scores and quality of life (Agache et al., 2020; Zhao et al., 2016; Maurer et al., 2013). Novel agents like ligelizumab (a next-generation anti-IgE), remibrutinib (a BTK inhibitor), and dupilumab (anti-IL-4Rα) show significant promise (Khan et al., 2025; Maurer et al., 2022; Metz et al., 2025; Maurer et al., 2022a). Cyclosporine, while effective, carries a less favorable safety profile (Grattan et al., 2000; Kulthanan et al., 2017). Emerging therapies such as barzolvolimab (anti-KIT) and TLL-018 (TYK2/JAK1 inhibitor) demonstrate encouraging early results (Maurer et al., 2023; Lu et al., 2024). Discussion: The evidence reveals a clear treatment hierarchy and elucidates dose-response relationships, time-to-onset profiles, and distinct safety-efficacy trade-offs. A key research gap is the lack of long-term comparative effectiveness data between newer agents (e.g., BTK inhibitors vs. biologics). Real-world data suggest omalizumab's efficacy is maintained in clinical practice, yet a substantial proportion of patients remain non-responsive to antihistamine-based regimens. Conclusion: The management of CSU has evolved significantly with targeted biologics and novel small molecules. Omalizumab remains the cornerstone of third-line therapy, while emerging agents offer new mechanisms of action. Future research should focus on head-to-head comparisons, long-term safety, predictive biomarkers for treatment selection, and strategies for managing complete non-responders.